U2 region of Epstein-Barr virus DNA may encode Epstein-Barr nuclear antigen 2. - Dambaugh, T (1984)
Sequence analysis of the U2 regions of the B95-8 and AG876 Epstein-Barr virus (EBV) isolates reveals divergence within a long open reading frame previously identified as encoding 1.5 kilobases of the 3' end of a viral RNA expressed in latently infected, growth-transformed, B-lymphocyte cell lines. Differences among EBV isolates within the U2 open reading frame are shown to correlate with differences in an EBV nuclear antigen, EBNA2. B95-8, W91, Raji, Cherry, and Lamont EBV isolates have similar U2 domains and encode similar-size EBNA2 proteins, while AG876, Jijoye, and P3HR-1 have variant or absent U2 domains and variant or absent EBNA2 proteins. The AG876 U2 open reading frame and EBNA2 protein are both shorter than those of B95-8. These data indicate that the U2 open reading frame encodes EBNA2.